1988
DOI: 10.3171/jns.1988.69.1.0115
|View full text |Cite
|
Sign up to set email alerts
|

Changes in periventricular vasculature of rabbit brain following induction of hydrocephalus and after shunting

Abstract: Hydrocephalus was induced in rabbits by injection of silicone oil into the cisterna magna. At 1 and 8 weeks postinjection the rabbits were either sacrificed or treated by cerebrospinal fluid shunting for 1 week. Blood vessel profiles in the periventricular neuropil were examined by light microscopy. In the caudate nucleus, septal area, and corpus callosum, hydrocephalus caused a reduction in the number of capillaries but no changes were observed in the number of larger blood vessels. Shunting reduced the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(58 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…Abbreviations NIRS, near-infrared spectroscopy HbO 2 , oxygenated Hb Hb, deoxygenated Hb HbD, Hb difference signal HbT, total Hb CytOx, oxidized cytochrome aa 3 ICP, intracranial pressure MAP, mean arterial pressure CPP, cerebral perfusion pressure CBF, cerebral blood flow rCBF, regional cerebral blood flow dpf, differential path-length factor Rational management of infantile hydrocephalus requires information about the disturbances in cerebral perfusion and metabolism that may contribute to the development of brain injury. Substantial evidence indicates that impairments of cerebral perfusion and metabolism play a role in the pathogenesis of brain injury secondary to hydrocephalus (1)(2)(3)(4)(5)(6)(7)(8). However, currently there are major limitations in the ability to define changes in cerebral hemodynamics and metabolism quantitatively, continuously, and noninvasively at the bedside of the human infant.…”
mentioning
confidence: 99%
“…Abbreviations NIRS, near-infrared spectroscopy HbO 2 , oxygenated Hb Hb, deoxygenated Hb HbD, Hb difference signal HbT, total Hb CytOx, oxidized cytochrome aa 3 ICP, intracranial pressure MAP, mean arterial pressure CPP, cerebral perfusion pressure CBF, cerebral blood flow rCBF, regional cerebral blood flow dpf, differential path-length factor Rational management of infantile hydrocephalus requires information about the disturbances in cerebral perfusion and metabolism that may contribute to the development of brain injury. Substantial evidence indicates that impairments of cerebral perfusion and metabolism play a role in the pathogenesis of brain injury secondary to hydrocephalus (1)(2)(3)(4)(5)(6)(7)(8). However, currently there are major limitations in the ability to define changes in cerebral hemodynamics and metabolism quantitatively, continuously, and noninvasively at the bedside of the human infant.…”
mentioning
confidence: 99%
“…We have also shown a sustained increase in BVd in the hippocampus after the induction of CH (Dombrowski et al, 2008). Although most studies have described cerebrovascular compression, a few studies have observed increased vascularity in certain brain regions and at various time points in hydrocephalus (Ransohoff et al, 1975;Del Bigio and Bruni, 1988;Jones et al, 1991). The size and direction of these observed BVd changes could not be explained by a simple spatial compression of an intact vascular tree.…”
Section: Cerebrovascular Changesmentioning
confidence: 50%
“…Although most studies have described cerebrovascular compression in CH (Del Bigio and Bruni, 1988), a few studies have observed increased vascular density in certain brain regions and at various time points in CH (Dombrowski et al, 2008;Luciano et al, 2001;Ransohoff et al, 1975). Previously, we have shown an initial decrease in vascularity followed by a return above baseline in cortical gray and periventricular white matter in CH .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Severity was classified as mild, moderate, and severe relative to each age group. This method has been used repeatedly in both clinical and experimental studies of hydrocephalus, 12,23 and exact measurements of the temporal changes that occur in HTX rats with progressive ventriculomegaly have been reported 24 and correlated with in vivo magnetic resonance imaging assessments of cortical mantle thickness. 19 …”
Section: Animal Populationmentioning
confidence: 99%